Authentic Versus Traditional Assessment: An Empirical Study Investigating the Difference in Seafarer Students' Academic Achievement. (12th July 2020) - Ghosh, Samrat; Brooks, Benjamin; Ranmuthugala, Dev; Bowles, Marcus
Abstract : Past research showed that traditional assessment methods that required seafarer students to construct responses based on memorisation and analysing information presented in absence of real-world contexts (e.g. oral examinations and multiple-choice questions) disengaged the students from learning. Memorising information is a lower-order cognitive ability, failure in which led to errors and low academic achievement for students. Authentic assessment methods require students to construct responses through the critical analysis of information presented in real-world contexts. Hence, this research investigated the difference in seafarer students' academic achievement (measured through scores obtained in assessment) in authentic assessment as compared with traditional assessment. Two separate and independent student groups (the 'control' group and 'treatment' group) were used for a selected unit of learning delivered at the Australian Maritime College within the Bachelor of Nautical Science degree program. Because some past researchers had defined and implemented traditional assessment methods as a single-occasion assessment, this project implemented the assessment in a summative format, as opposed to authentic assessments implemented during student preparation. Analysis of student scores revealed that the authentically assessed students were guided towards significantly higher academic achievement.